2011
DOI: 10.1021/jp1095294
|View full text |Cite
|
Sign up to set email alerts
|

Initial Excited-State Structural Dynamics of 9-Methyladenine from UV Resonance Raman Spectroscopy

Abstract: The photophysics and photochemistry of nucleobases are the factors governing the photostability of DNA and RNA, since they are the UV chromophores in nucleic acids. Because the formation of photoproducts involves structural changes in the excited electronic state, we study here the initial excited-state structural dynamics of 9-methyladenine (9-MeA) by using UV resonance Raman (UVRR) spectroscopy. UV resonance Raman intensities are sensitive to the initial excited-state structural dynamics of molecules. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…6,9,11,12 Spectral slit widths were 5−7 cm −1 . Spectral line widths are larger than the slit bandwidth due to broadening by the laser source and subsequent frequency multiplication.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9,11,12 Spectral slit widths were 5−7 cm −1 . Spectral line widths are larger than the slit bandwidth due to broadening by the laser source and subsequent frequency multiplication.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The general implementation of these equations for absorption and resonance Raman spectroscopy have been described in detail previously. [4][5][6][7][8][9][10][11][12][13][14]16,17 The vibrational mode assignments described in Tables 1 and 2 were obtained by DFT computation at the B3LYP/6-311G(d,p) level of theory, with the default gradients implemented in the Gaussian09 18 package performed on the initial planar C s structures of uracil and 6-MeU in the diketo tautomer form. The isotope effect was calculated for 6-d-U from the uracil frequencies, which are not scaled.…”
Section: ■ Theorymentioning
confidence: 99%
“…The observed decrease in the initial excited‐state dynamics has been attributed to the presence of less‐steep excited‐state potential energy surfaces and a shift in the potential energy surface at the Frank–Condon region in nucleosides . The initial excited‐state structural dynamics of 2′‐deoxyguanosine and 9‐methyladenine were studied and are consistent with their resulting photochemistry for corresponding nucleobases. Adenine and guanosine nucleobases are not as photochemically active as the pyrimidine nucleobases, and the resonance Raman intensities and resulting initial excited‐state structural dynamics of their respective nucleosides are also smaller than those of the pyrimidines, further suggesting a positive correlation between steepness of the potential energy surface and photochemical quantum yield.…”
Section: Introductionmentioning
confidence: 74%
“…Thus, there is a possibility of forming various photoproducts. Previous studies have shown that UVC irradiation of DNA strands containing “AATTAA” would produce the AA and TA photoproducts, along with the CPD and [6‐4] PP. However, the AA and TA photochemical yields are at most only 10% of those of TT, making these products much less probable .…”
Section: Resultsmentioning
confidence: 99%